A structural comparison of casein micelles in cow, goat and sheep milk using X-ray scattering. Issue 17 (16th April 2018) - Ingham, B.; Smialowska, A.; Kirby, N. M.; Wang, C.; Carr, A. J.
Abstract : The casein micelle is a flexible construct, with its key structural components being casein proteins and colloidal calcium phosphate nanoclusters. Abstract : The casein micelle is a flexible construct, with its key structural components being casein proteins and colloidal calcium phosphate nanoclusters. According to literature, milk from different species exhibits differences in composition and physicochemical properties. X-ray scattering techniques were used to investigate and compare the nanoscale structure of casein micelles present in cow, goat and sheep milk. Although there were differences in the size and density of larger scale protein structures, at an atomic level the protein structures were similar. There were also strong similarities in the structure of the calcium-containing nanoclusters, namely that they had similar sizes and separations within the casein micelle for all three species.